Can the Random Walk be beat on the Forex Market? - Richard de Vesvrotte, Hubert (2015)
The purpose of this paper is to propose to challenge the Random Walk as predictor of the variations of spot rates. The Random walk will be tested again the following models: UIP, PPP, MF, Asymmetric Taylor Rule, Symmetric Taylor Rule. Using an out-sample methodology; it will be applied rolling and recursive regressions in order to set up the predictive models. The tests applied confirmed the supremacy of the PPP and the Asymmetric Taylor Rule on the Random Walk and the failure of the MF. I showed that the best model is the Asymmetric Taylor Rule.